Bheeram, Vema Reddy - (:unkn) unknown (My University, 2026)
Dr. Vema Reddy Bheeram received his Bachelor of Science degree (2011) from Osmania University and Master of Science degree (2015) in Chemistry from GITAM University, India. He earned his Doctor of Philosophy degree in Chemistry from UGC-DAE-CSR, Kolkata and GITAM University (2020), India. During his PhD training, he was actively involved in the development of optical device and biomedical technologies, particularly based on nanotechnology innovations, for potential optoelectronic and biomedical applications. His research mainly involves the novel lanthanide based luminescent metal organic frameworks (Ln-MOFs) and solid state nanophosphor materials for various new generation multi-functional optoelectronic and biomaterials with unique properties.
Keywords: Luminescent Nanomaterials, Inorganic Materials, Lanthanide doped Upconversion Nanoparticles, Optoelectronic Materials, Nanophosphors, Lanthanide Metal Organic Frameworks (Ln-MOFs), Coordination Chemistry, X-ray Crystallography, Nanophotonics, Biomedical Imaging, Drug delivery; chemistry; materials